Answer:
D
Step-by-step explanation:
Given the 2 equations
4x - 5y = 18 → (1)
3x - 2y = 10 → (2)
Multiplying (1) by 3 and (2) by - 4, then adding will eliminate the x- term
12x - 15y = 54 → (3)
- 12x + 8y = - 40 → (4)
Add (3) and (4) term by term to eliminate x, that is
- 7y = 14 ( divide both sides by - 7 )
y = - 2
Substitute y = - 2 into either of the 2 equations and solve for x
Substituting into (1)
4x - 5(- 2) = 18
4x + 10 = 18 ( subtract 10 from both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is (2, - 2 ) → D
Answer:
maybe rotation.........i think....
Hey, can you please fix this question? I can't seem to understand it. When you do, please tell me so I can help you out!
Answer:
D is false
Step-by-step explanation:
Answer:
9.5
Step-by-step explanation:
(0.5^2 + 0.5^-2 + 0.5) / 0.5 = 9.5
Hope this help! :)